Abnormal function of the vasopressin-cyclic-AMP-aquaporin2 axis during urine concentrating and diluting in patients with reduced renal function. A case control study - Pedersen, Erling B; Thomsen, Ingrid M; Lauridsen, Thomas G (BMC nephrology, 2010)
The kidneys ability to concentrate and dilute urine is deteriorated during progressive renal insufficiency. We wanted to test the hypothesis that these phenomena could be attributed to an abnormal function of the principal cells in the distal part of the nephron. Healthy control subjects and patients with chronic kidney diseases were studied. Group 1 comprised healthy subjects, n = 10. Groups 2-4 comprised patients with chronic kidney disease (Group 2, n = 14, e-GFR ≤ 90 m1/min; Group 3, n = 11, 60 m1/min ≤ e-GFR < 90 ml/min; and Group 4, n = 16, 15 ml/min ≤ e-GFR < 60 ml/min). The subjects collected urine during 24 hours. A urine concentrating test was done by thirsting during the following 12 hours. Thereafter, a urine diluting test was performed with a water load of 20 ml/kg body weight. The effect variables were urinary excretions of aquaporin2 (u-AQP2), cyclic-AMP (u-c-AMP), urine volume (UV), free water clearance (CH2O), urine osmolarity (u-Osm), and plasma arginine vasopressin (p-AVP). After fluid deprivation, u-Osm increased. In all groups, UV and CH2O decreased and u-AQP2 and u-c-AMP increased in Groups 1 and 2, but were unchanged in Group 3 and 4. P-AVP was significantly higher in Group 4 than in the other groups. During urine diluting, UV and CH2O reached significantly higher levels in Groups 1-3 than Group 4. Both before and after water loading, u-AQP2 and p-AVP were significantly higher and u-c-AMP was significantly lower in Group 4 than the other groups. Estimated-GFR was correlated negatively to p-AVP and positively to u-c-AMP. Patients with moderately severe chronic kidney disease have a reduced renal concentrating and diluting capacity compared to both patients with milder chronic kidney disease and healthy control subjects. These phenomena can be attributed, at least partly, to an abnormally decreased response in the AVP-c-AMP-AQP2 axis.ClinicalTrials.Gov Identifier: NCT00313430.